Ethics in qualitative research - Miller, Tina, 1957- (Los Angeles, California : London : SAGE, 2012)
"This fresh, confident Second Edition expands its focus on the theoretical and practical aspects of doing qualitative research in light of new ethical dilemmas facing researchers today. In a climate of significant social and technological change, researchers must respond to increased ethical regulation and scrutiny of research. New sources, types of data and modes of accessing participants are all challenging and reconfiguring traditional ideas of the research relationship. This engaging textbook explores key ethical dilemmas - including research boundaries, informed consent, participation, rapport and analysis - within the context of a rapidly changing research environment. The book effectively covers the ethical issues related to the data collection process, helping readers to address the ethical considerations relevant to their research."--Publisher's website.
Ethics and feminist research: theory and practice / Rosalind Edwards and Melanie Mauthner -- Reconfiguring research relationships: regulation, new technologies and doing ethical research / Tina Miller -- The ethics of intention: research as a political tool / Val Gillies and Pam Alldred -- Consenting to what? Issues of access, gate-keeping and 'informed' consent / Tina Miller and Linda Bell -- Divided loyalties, divided expectations: research ethics, professional and occupational responsibilities / Linda Bell and Linda Nutt -- Encouraging participation: ethics and responsibilities / Maxine Birch and Tina Miller -- 'Doing rapport' and the ethics of 'faking friendship' / Jean Duncombe and Julie Jessop -- Knowing responsibly: ethics, feminist epistemologies and methodologies / Andrea Doucet and Natasha S. Mauthner -- Eliciting research accounts: re/producing modern subjects? / Pam Alldred and Val Gillies -- 'Accounting for our part of the entangled webs we weave': ethical and moral issues in digital data sharing / Natasha S. Mauthner -- Conclusions: navigating ethical dilemmas and new digital horizons / Melanie Mauthner, Maxine Birch, Tina Miller and Julie Jessop.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Social sciences -- Research -- Moral and ethical aspects; Social sciences -- Methodology -- Moral and ethical aspects; Feminist ethics; Qualitative research -- Moral and ethical aspects; Electronic books